Relationship Between Metacognitive Strategies and Motivation for Critical Thinking in Pedagogy Students from three Chilean Universities : Relación entre estrategias metacognitivas y motivación al pensamiento crítico en estudiantes de pedagogía de tres universidades chilenas (Papeles, 2025)
Introduction: Critical thinking is a relevant competency in the training of children and adolescents, considered as part of the competencies of the 21st century. It is a complex construct, and it has defined as a skill that is strengthened by metacognition and motivation; However, no in-depth study has been made of how these variables are related. This study was carried out in order to analyze the relationship between metacognitive strategies and motivation for critical thinking in pedagogy students at three higher education institutions in south-central Chile, in order to delve into the empirical relationship between the variables. Methodology: A non-experimental study, with a descriptive and correlational design was carried out; 435 pedagogy students from three higher education institutions in central-southern Chile participated in the study. The instruments applied were the O’Neill and Abedi metacognitive strategies questionnaire, and the Valenzuela critical thinking motivation questionnaire. Results and discussions: A very high level of perceived performance is observed in the two variables, as well as positive, significant and moderately strong relationships between both, both at a general level (r = 0.545, p
Keywords: Cognition; Higher Education; motivation; educational psychology; critical thinking